The three-dimensional structure of a helix-less variant of intestinal fatty acid-binding protein. - Steele, R. A. (Cold Spring Harbor Laboratory Press, 1998)
Intestinal fatty acid-binding protein (I-FABP) is a cytosolic 15.1-kDa protein that appears to function in the intracellular transport and metabolic trafficking of fatty acids. It binds a single molecule of long-chain fatty acid in an enclosed cavity surrounded by two five-stranded antiparallel beta-sheets and a helix-turn-helix domain. To investigate the role of the helical domain, we engineered a variant of I-FABP by deleting 17 contiguous residues and inserting a Ser-Gly linker (Kim K et al., 1996, Biochemistry 35:7553-7558). This variant, termed delta17-SG, was remarkably stable, exhibited a high beta-sheet content and was able to bind fatty acids with some features characteristic of the wild-type protein. In the present study, we determined the structure of the delta17-SG/palmitate complex at atomic resolution using triple-resonance 3D NMR methods. Sequence-specific 1H, 13C, and 15N resonance assignments were established at pH 7.2 and 25 degrees C and used to define the consensus 1H/13C chemical shift-derived secondary structure. Subsequently, an iterative protocol was used to identify 2,544 NOE-derived interproton distance restraints and to calculate its tertiary structure using a unique distance geometry/simulated annealing algorithm. In spite of the sizable deletion, the delta17-SG structure exhibits a backbone conformation that is nearly superimposable with the beta-sheet domain of the wild-type protein. The selective deletion of the alpha-helical domain creates a very large opening that connects the interior ligand-binding cavity with exterior solvent. Unlike wild-type I-FABP, fatty acid dissociation from delta17-SG is structurally and kinetically unimpeded, and a protein conformational transition is not required. The delta17-SG variant of I-FABP is the only wild-type or engineered member of the intracellular lipid-binding protein family whose structure lacks alpha-helices. Thus, delta17-SG I-FABP constitutes a unique model system for investigating the role of the helical domain in ligand-protein recognition, protein stability and folding, lipid transfer mechanisms, and cellular function.